We Say “Reunite with Your Pure Heart” to our Patient who Will Undergo Kidney Transplantation - Shafa Shahbazova; Rashad Shahvaladov (Caucasian Medical Journal)
Permanent hemodialysis catheters are reguarly used in stage V chronic kidney disease patients undergoing hemadialysis, but their long stay in the body can result in infection, sepsis and thrombus formation in the right atrium. Hemodialysis catheter-related right atrial thrombus is a rare complication but can lead to serious complications. Intracardiac thrombus can be asymptomatic in hemodialysis patients, and it can manifest itself with fever, shortness of breath, chest pain, and even sudden death due to pulmonary embolism.